(3eYQaI cjajI GdCQUGO hGdYed HPGJ GdMdb dHWdjehSs - (3CMeO Hf YHO Gddg, MHT GdMGSH GdeQhRjs
(3ChdgG (B:s
(3gPg GdBdI PcQgG GdaGVd HWdjehS ai cJGH GdeLSWi hJYi PGJ GdMdb hgh eDdaI ef SJ Mdb s
(3BNQgG (B:s
(3heGhGab ef MdbI GdCab aeG Hjfg hHjf eWGdY GdMed ef gPg GdMdbI hYdi gPG jecf Yed SGFQ GdCYeGd Je GdYed HPGJ GdMdb dHWdjehS hHGddg GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3cJHJ Hbde eged GdfbW GMjGfkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3475( 2(3H(B)) s
Keywords: (3Gdadcs